The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.08.11.553031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Second Harmonic Generation Imaging Reveals Entanglement of Collagen Fibers in the Elephant Trunk Skin Dermis

Abstract: Form-function relationships often have tradeoffs: if a material is tough, it is often inflexible, and vice versa. This is particularly relevant for the elephant trunk, where the skin should be protective yet elastic. To investigate how this is achieved, we used classical histochemical staining and second harmonic generation microscopy to describe the morphology and composition of elephant trunk skin. We report structure at the macro and micro scales, from the thickness of the dermis to the interaction of 10 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It has been shown that the distal dorsal part of the trunk contributes the most to trunk stretching and that the ventral side stretches comparably little when the trunk is extended 1 . The distal ventral trunk has been described to be used in sweeping food together 9 and most trunk manipulation movements are accomplished with gripping and grabbing on the ventral side 54 . Specifically, the trunk section just before the trunk tip is used in holding food or other objects, often between the lateral skin ridges that go along the ventral trunk and that have a very high density of whiskers in this distinct trunk part 49 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the distal dorsal part of the trunk contributes the most to trunk stretching and that the ventral side stretches comparably little when the trunk is extended 1 . The distal ventral trunk has been described to be used in sweeping food together 9 and most trunk manipulation movements are accomplished with gripping and grabbing on the ventral side 54 . Specifically, the trunk section just before the trunk tip is used in holding food or other objects, often between the lateral skin ridges that go along the ventral trunk and that have a very high density of whiskers in this distinct trunk part 49 .…”
Section: Discussionmentioning
confidence: 99%
“…This skin has a protective function, but elephants also utilize it to assist in gripping objects when they wrap 6 or sweep food using the wrinkled ventral portion at the tip of the trunk 7 . Elephant skin is known for some simple gross mechanical properties, such as a cracked epidermis for thermoregulation 8 in African elephants and entangled collagen in the dermis of the trunk for added protection and extension 9 . The trunk's mobility and flexibility are enabled by a highly complex musculature [10][11][12] , controlled by a very elaborate motor nucleus 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation